Collaborative Governance and Effectiveness of Vocational Training and Graduate Job Placement: An Ansell and Gash Perspective - Darmawansyah; Nurliah Nurdin; Muhammad Taufiq; R Luki Karunia (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2026)
Vocational training in Indonesia, specifically at the Vocational Training and Productivity Center (VPTC) in Samarinda and Makassar, continues to struggle with suboptimal graduate employability. This research identifies a critical disconnect between institutional training and industrial demand, rooted in fragmented multi-stakeholder collaboration. Using the Ansell and Gash (2008) Collaborative Governance framework, this study analyzes the governance dynamics hindering effective job placement. Employing a qualitative multi-site case study approach—comprising document analysis, Focus Group Discussions (FGD), and field observations—the findings reveal a